2011
DOI: 10.1152/physiolgenomics.00248.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vivo transfection with anti-miR-214 on gene expression in murine molar tooth germ

Abstract: MicroRNAs (miRNAs) are an abundant class of noncoding RNAs that are believed to be important in many biological processes through regulation of gene expression. Little is known of their function in tooth morphogenesis and differentiation. MicroRNA-214 (miR-214), encoded by the polycistronic Dnm30os gene, is highly expressed during development of molar tooth germ and was selected as a target for silencing with anti-miR-214. Mandibular injection of 1-100 pmol of anti-miR-214 close to the developing first molar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
(41 reference statements)
0
29
0
Order By: Relevance
“…A missense mutation of the initiator methionine codon prevents translation of HMGA1P7 whereas HMGA1P6 is non-protein coding since it carries a mutation in the stop codon and so generates a non-translatable mRNA. Within the high homology regions, we found perfectly conserved seed matches for miRNAs that have been predicted (miR-103, miR-142-3p, miR-370, and miR-432) or already demonstrated (miR-15 [31], miR-16 [31], miR-26a [32], miR-214 [33], miR-548c-3p [34] and miR-761 [33]) to target the HMGA1 gene (Figure 1B and 1C). …”
Section: Resultsmentioning
confidence: 74%
“…A missense mutation of the initiator methionine codon prevents translation of HMGA1P7 whereas HMGA1P6 is non-protein coding since it carries a mutation in the stop codon and so generates a non-translatable mRNA. Within the high homology regions, we found perfectly conserved seed matches for miRNAs that have been predicted (miR-103, miR-142-3p, miR-370, and miR-432) or already demonstrated (miR-15 [31], miR-16 [31], miR-26a [32], miR-214 [33], miR-548c-3p [34] and miR-761 [33]) to target the HMGA1 gene (Figure 1B and 1C). …”
Section: Resultsmentioning
confidence: 74%
“…MiR-200b and miR-200c are both important regulatory miRNAs, but only miR-200b regulates the porcine TGF-beta signaling pathway. MiR-214 is the most highly expressed miRNA, and the most likely “tooth-specific” miRNA, but recent studies of the role of miR-214 in tooth germs suggest that miR-214 indirectly affects amelogenesis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the crystal microstructure might not be detectable by eye or with a stereomicroscope. A recent study using in vivo transfection of anti-miR214 also showed no obvious enamel morphological changes observed with a stereomicroscope, but further SEM analysis indicated alterations in the prism decussation structure (59).…”
Section: Discussionmentioning
confidence: 91%